2008
DOI: 10.1108/17556228200800014
|View full text |Cite
|
Sign up to set email alerts
|

Introducing skills for psychosocial interventions into undergraduate mental health nurse education

Abstract: This paper describes how psychosocial interventions (PSI) have been integrated into an undergraduate mental health nursing programme. The first part of the paper provides the broad context of PSI in nurse education and justifies the need to incorporate skills for PSI into the undergraduate nursing curriculum. A variety of educational theories and research are presented, which have informed the development, structure and delivery of the skills programme underpinned by PSI into the undergraduate programme. The s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0
2

Year Published

2009
2009
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 27 publications
0
6
0
2
Order By: Relevance
“…Perhaps, the introduction of undergraduate PSI training as outlined by Stacey and Rayner (2008) merits closer attention. The profile of participants revealed that they mainly worked in community multidisciplinary teams with just 13Á5% based in acute inpatient settings.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Perhaps, the introduction of undergraduate PSI training as outlined by Stacey and Rayner (2008) merits closer attention. The profile of participants revealed that they mainly worked in community multidisciplinary teams with just 13Á5% based in acute inpatient settings.…”
Section: Discussionmentioning
confidence: 99%
“…Yet, their explanatory comments were replete with references that training in PSI provided 'exactly the knowledge I required to do my job' (P25). Perhaps, the introduction of undergraduate PSI training as outlined by Stacey and Rayner (2008) merits closer attention.…”
Section: Discussionmentioning
confidence: 99%
“…However, most mental health professionals in the UK still complete their pre‐registration training without specific skills training in working with families (Stacey and Rayner, ). This leaves staff lacking in confidence and ill‐equipped to engage with families on the routine basis envisaged by national policy.…”
Section: Needs Of Families and Carersmentioning
confidence: 99%
“…Second, most mental health professionals still complete their pre‐registration training without specific skills training in working with families (Stacey and Rayner, 2008). This leaves staff ill equipped and lacking in confidence to engage with families on the routine basis envisaged by national policy.…”
Section: Why Is There a Need For A Staff Training Programme?mentioning
confidence: 99%